UPAYA GURU AKIDAH AKHLAK DALAM MEMBENTUK AKHLAKUL KARIMAH SISWA DI MTS ARADAL-HAQ DESA PEMATANG LUMUT KECAMATAN BETARA KABUPATEN TANJUNG JABUNG BARATPROVINSI JAMBI - Hasan Abdul Wahid; M. Thontawi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the efforts of Akidah Akhlak teachers in shaping students' good character at MTs Aradal-Haq Pematang Lumut in Jambi Province, the obstacles faced in its implementation, and the results achieved from these efforts. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation with the main informants being Akidah Akhlak teachers, supported by the head of the madrasah and students of MTs Aradal-Haq Pematang Lumut. Data analysis was carried out in three stages, namely data reduction, data presentation, and conclusion drawing. The results of the study show that Akidah Akhlak teachers play an active role in shaping students' akhlakul karimah through various efforts, including setting an example, instilling good and religious behavior, providing advice and motivation, relating Akidah Akhlak material to everyday life, and providing educational reprimands and sanctions. The obstacles faced by Akidah Akhlak teachers include differences in students' family and environmental backgrounds, low awareness and discipline among some students, the influence of social circles and social media, limited learning time, and a lack of cooperation with some parents. Nevertheless, various consistent and continuous guidance efforts have shown positive results, marked by an increase in politeness, discipline, responsibility, awareness of worship, and the formation of positive behavioral habits in students' daily lives. Thus, the role of Akidah Akhlak teachers has proven to be very important and strategic in nurturing character and instilling akhlakul karimah values in students at MTs Aradal-Haq Pematang Lumut, Jambi Province.